Optimización del proceso productivo de chocolate en tablilla en la microempresa chocolates Monge - Olmos Escobar, Walter Stalyn (2019)
The following research project consist in doing a study of the times and movements for the production of splintered chocolate, in the micro – enterprise “MONGE CHOCOLATES” with the purpose of improving the process of making splinter chocolate, in this way the process were identified by the creation of a diagram of productive process that allowed to know in detail the process to consider a possible optimization in the micro enterprise , surveys were carried out with a series of questions that allowed to determine how the product is in the market where the product being in great demand and has the possibility of expansion so it is necessary to optimize the production process. The information was collected from each production area in order to obtain the times of the process allowing to know where there are bottlenecks, with the records of the data obtained it was preceded to carry out the study of times according to the methodology of return to zero for time studier, to determinate a standard time out home work area considering the work rate of each employee and considering the supplements for each task, in which two process there are carried out with a high production time seeing these weaknesses, a proposal for the implementation of a mixing machine and the repair of an existing molding machine were made, with the proposal already embodied, the time study was carried out again obtaining favorable results for the production, because it was evidenced that the productivity increased by a considerable percentage and the gains will also increase, in addition the time recovery of the investment of the proposal will considerable in a period of time.